2022
DOI: 10.1002/chem.202201543
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide‐Responsive Triggers Based on Borinic Acids: Molecular Insights into the Control of Oxidative Rearrangement

Abstract: Supporting information for this article is given via a link at the end of the document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…All three oxygen reactive species (hypochlorous acid, hydrogen peroxide, and peroxynitrite) can cleave the arylboronic acid trigger, which acts as a receptor for photoinduced electron transfer in the buffer. The phenylboronic acid cleaved and formed a phenol derivative that exhibited intramolecular charge transfer (ICT) depending on pH and other microenvironments [ 45 ]. For a systematic study, a time-dependent kinetics reaction was recorded by monitoring at 400 nm the maximum absorbance in UV spectra for 80 min after adding 100 µM H 2 O 2 and HOCl ( Figures S2 and S3 ).…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…All three oxygen reactive species (hypochlorous acid, hydrogen peroxide, and peroxynitrite) can cleave the arylboronic acid trigger, which acts as a receptor for photoinduced electron transfer in the buffer. The phenylboronic acid cleaved and formed a phenol derivative that exhibited intramolecular charge transfer (ICT) depending on pH and other microenvironments [ 45 ]. For a systematic study, a time-dependent kinetics reaction was recorded by monitoring at 400 nm the maximum absorbance in UV spectra for 80 min after adding 100 µM H 2 O 2 and HOCl ( Figures S2 and S3 ).…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…134 Recent follow-up work detailed the synthesis of a more general trigger derivative that was further modified to overcome challenges related to the regioselectivity of oxidative deprotection. 136 Another direction is in catalytic activity-based sensing where one uncaging event can lead to multiple signal outputs. This strategy is highlighted by elegant work from Shabat and colleagues on self-immolative polymer scaffolds that can be uncaged by a single boronate oxidation or systems by Phillips that self-sustain peroxide consumption and generation for continuous detection.…”
Section: T H Imentioning
confidence: 99%
“…The reported borinic-acid-based coumarin was selective for H 2 O 2 over other ROS and exhibited a significantly faster turn-on response in live COS7 gp91/p22 . Recent follow-up work detailed the synthesis of a more general trigger derivative that was further modified to overcome challenges related to the regioselectivity of oxidative deprotection . Another direction is in catalytic activity-based sensing where one uncaging event can lead to multiple signal outputs.…”
Section: Outlook and Future Directionsmentioning
confidence: 99%
“…1B). 35 Graham and co-workers showed that neighboring functionality can dramatically change arylboronic oxidation rates. 30 For instance, o-carboxyphenylboronic acid cyclizes to a boronolactone, which slows its H2O2-mediated oxidation by more than 5-orders of magnitude (Fig.…”
mentioning
confidence: 99%